The mental health of all children in contact with social services: a population-wide record-linkage study in Northern Ireland - Sarah McKenna; Dermot O'Reilly; Aideen Maguire (Cambridge University Press, 2023)
Abstract Aims Children in contact with social services are at high risk for mental ill health, but it is not known what proportion of the child population has contact with social services or how risk varies within this group compared to unexposed peers. We aim to quantify the extent and nature of contact with social services within the child population in Northern Ireland (NI) and the association with mental ill health. We also examine which social care experiences identify those most at risk. Methods This is a population-based record-linkage study of 497,269 children (aged under 18 years) alive and resident in NI in 2015 using routinely collected health and social care data. Exposure was categorized as (1) no contact, (2) referred but assessed as not in need (NIN), (3) child in need (CIN) and (4) child in care (CIC). Multilevel logistic regression analyses estimated odds ratios (ORs) for mental ill health indicated by receipt of psychotropic medication (antidepressants, anxiolytics, antipsychotics and hypnotics), psychiatric hospital admission and hospital-presenting self-harm or ideation. Results Over one in six children (17.2%, n = 85,792) were currently or previously in contact with social services, and almost one child in every 20 (4.8%, n = 23,975) had contact in 2015. Likelihood of any mental ill health outcome increased incrementally with the level of contact with social services relative to unexposed peers: NIN (OR 5.90 [95% confidence interval (CI) 5.10-6.83]), CIN (OR 5.99 [95% CI 5.50-6.53]) and CIC (OR 12.60 [95% CI 10.63-14.95]). All tiers of contact, number of referrals, number of care episodes and placement type were strongly associated with the likelihood of mental ill health. Conclusion Children who have contact with social services account for a large and disproportionate amount of mental ill health in the child population. Likelihood of poor mental health across indicators is highest in care experienced children but also extends to the much larger population of children in contact with social services but never in care. Findings suggest a need for targeted mental health screening and enhanced support for all children in contact with social services.